An application of trigeneration and its economic analysis - Temir, G; Bilge, D; Emanet, O (TAYLOR & FRANCIS INC, 2004)
Trigeneration can be described as the production of three different forms of energy-power heat, and coldness together Trigeneration increases the productivity and the services provided by cogeneration installations. Consequently, the production costs of the systems related with energy consumption become lower For this purpose, a trigeneration application has been carried out based on the data of a currently active insulated pipe production plant situated in Istanbul, Turkey. In the feasibility study made after calculations, the profitability and payback period have been calculated.
Keywords: cogeneration; energy saving; trigeneration; Energy & Fuels; Engineering